Les pensionnats et foyers autochtones fédéraux du Canada : la commémoration des lieux de mémoire sensible selon une visée réconciliatoire - Lemay-Perreault, Rébéca; Paquin, Maryse; Desgagné, Gabrielle (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2023)
Some years ago Canada began a process of reconciliation with First Peoples, undertaking the difficult task of acknowledging its colonial and racist past. Recent news, particularly the discovery of unmarked graves on the grounds of former federal residential schools, marking the system as a symbol of Canadian colonialism, brings us face to face collectively with this reality, a less than sterling era in our history. Museums and national heritage sites can, through their exhibitions, help to show the history and consequences of the federal residential schools, by institutionalizing and integrating them in the Canadian national narrative. While acknowledging this darker side of Canadian history seems vital to the process of reconciliation between Indigenous and non- Indigenous peoples, commemorating sensitive spaces of memory is equally important. The survival of this sensitive memory seeks to better know and understand the history and consequences of the federal residential schools. Yet it is understood that no heritage or museum institution is free of its ideological past. In this context, how is it possible to ensure that this new thread of the story is woven into the fabric of our national history? How can we prevent colonial ramifications from being transformed into a new instrument of domination? What stumbling blocks lie in the way of commemoration with a goal of reconciliation regarding the sensitive spaces of memory which are the federal residential schools? These questions can all affect the process of reconciliation between Indigenous and non-Indigenous peoples in the country. Within the scope of this edition on inclusive participation, this article brings forward a discussion of the approaches, means and conditions for initiating the commemoration of the sensitive spaces of memory which are the federal residential schools, aiming for reconciliation. It also touches on the hurdles facing this effort. It presents a synthesis of research, an attempt to examine the operational principles of the national narrative and of commemoration. After a brief presentation of the contextual setting, two fundamental non-Indigenous principles implied in this context are presented, as well as their conceptual constellation. The first is the “duty of remembrance.” While it is essential in every commemorative effort since the Second World War, it is hard to see the emphasis placed on acknowledging the status of “victim” as compatible with the importance accorded to healing of Indigenous Peoples aiming, conversely, to transcend stigma. The second impediment lies within the principle of universalism, which is fundamental to all Western institutions–science, democracy, education, cultural accessibility, political programs, etc. Socially justified as a principle of equity, diversity and inclusion, universalism has a perverse effect which may dilute the regional and community characteristics of the commemoration of federal residential schools. It does so by smoothing out the diversity of the memories that the institutions choose to share and disseminate or to suppress and forget certain aspects, as well as the method of commemorating and patrimonializing them, and above all with whom. Thus, without prescribing a concrete or single solution, this article aims to shed light on the pitfalls inherent in the effort to commemorate the history and consequences of the federal residential schools, to institutionalize them and integrate them into the Canadian national narrative, in a spirit of critical self-awareness.